84.1k views
4 votes
Find the roots of the quadratic equation 3y² - 4y+1=0 By

i) completing the square method

ii) the formula​

User Mvinayakam
by
5.4k points

1 Answer

2 votes

Answer:

i)
3y^2 -4y +1=0

We can divide both sides of the equation by 3 and we got:


y^2 -(4)/(3)y +(1)/(3)=0

Now we can complete the square and we got:


(y^2 -(4)/(3)y +(4)/(9)) +((1)/(3) -(4)/(9))=0


(y- (2)/(3))^2 =(1)/(9)

We take square root on both sides and we got:


y-(2)/(3)= \pm (1)/(3)

And the solutions for y are:


y_1 = (1)/(3) +(2)/(3)=1


y_1 = -(1)/(3) +(2)/(3)=(1)/(3)

ii)
y =(-b \pm √(b^2 -4ac))/(2a)

And with
a = 3, b=-4 and c =1 we got:


y =(4 \pm √((-4)^2 -4(3)(1)))/(2*3)

And we got:


y_1 = 1 , y_2 =(1)/(3)

Explanation:

Part i

For this case we have the following function given:


3y^2 -4y +1=0

We can divide both sides of the equation by 3 and we got:


y^2 -(4)/(3)y +(1)/(3)=0

Now we can complete the square and we got:


(y^2 -(4)/(3)y +(4)/(9)) +((1)/(3) -(4)/(9))=0


(y- (2)/(3))^2 =(1)/(9)

We take square root on both sides and we got:


y-(2)/(3)= \pm (1)/(3)

And the solutions for y are:


y_1 = (1)/(3) +(2)/(3)=1


y_1 = -(1)/(3) +(2)/(3)=(1)/(3)

Part ii

We can use the quadratic formula:


y =(-b \pm √(b^2 -4ac))/(2a)

And with
a = 3, b=-4 and c =1 we got:


y =(4 \pm √((-4)^2 -4(3)(1)))/(2*3)

And we got:


y_1 = 1 , y_2 =(1)/(3)

User Abhay Singh
by
5.9k points